Proteinuria as a Biomarker for COVID-19 Severity - Ouahmi, Hajar; Courjon, Johan; Morand, Lucas; François, Juliette; Bruckert, Vincent; Lombardi, Romain; Esnault, Vincent; Seitz-Polski, Barbara; Demonchy, Elisa; Dellamonica, Jean; Boyer-Suavet, Sonia (Frontiers in Physiology, 2021)
Background: Renal involvement in SARS-CoV-2 infection has been retrospectively described, especially acute kidney injury (AKI). However, quantitative proteinuria assessment and its implication in COVID-19 remain unknown. Methods: In this prospective, multicenter study in France, we collected clinical and biological data including urinary protein to creatine ratio (UPCR) in patients presenting with moderate to severe COVID-19. Clinical outcome was analyzed according to the level of UPCR. Results: 42 /45 patients (93.3%) had renal involvement (abnormal urinary sediment and/or AKI). Significant proteinuria occurred in 60 % of patients. Urine protein electrophoresis showed tubular protein excretion in 83.8% of patients with proteinuria. Inflammatory parametersand D-dimer concentrations correlated with proteinuria level. Patients who required intensive care unit (ICU) admission had higher proteinuria (p = 0.008). On multivariate analysis, proteinuria greater than 0.3 g/g was related to a higher prevalence of ICU admission (OR=4.72, IC95 (1.16- 23.21), p = 0.03), acute respiratory distress syndrome (ARDS) (OR=6.89, IC95 (1.41-53.01, p = 0.02), nosocomial infections (OR=3.75, IC95 (1.11-13.55), p = 0.03), longer inpatient hospital stay (p = 0.003). Conclusion: Renal involvement is common in moderate to severe SARS-CoV-2 infection. Proteinuria at baseline is an independent risk factor for increased hospitalization duration and ICU admission in patients with COVID-19.